ASPEK LINGKUNGAN SEBAGAI FAKTOR PENENTU KEBERHASILAN BUDIDAYA JAMUR TIRAM (PLEUROTUS SP) - Netty Widyastuti (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Environment aspect as requirement growing of oyster mushroom (Pleurotus sp.), give priority like temperature, relative humidity, time, CO2 and light. The parameter have different influence to each stadium or stage, for example mycelia growing on substrate, formation of fruiting primordia, formation of fruiting body, harvest cycle and BER (Biological Efficiency Ratio) value. pH medium have to regulated (betweenN6-7), incubation phase (22 - 28 O C ), humidity 60-70% and fruiting body phase 16 -N22 O C. Growing mycelium without light, growing fruiting body is needed light stimulant, light intensity 60 - 70 %.